The importance of correcting for variable probe–sample interactions in AFM-IR spectroscopy: AFM-IR of dried bacteria on a polyurethane film. Issue 16 (12th July 2016) - Barlow, Daniel E.; Biffinger, Justin C.; Cockrell-Zugell, Allison L.; Lo, Michael; Kjoller, Kevin; Cook, Debra; Lee, Woo Kyung; Pehrsson, Pehr E.; Crookes-Goodson, Wendy J.; Hung, Chia-Suei; Nadeau, Lloyd J.; Russell, John N.
Abstract : Interplay between AFM-IR probe – sample interactions and signal transduction for bacteria – PU bilayer. Abstract : AFM-IR is a combined atomic force microscopy–infrared spectroscopy method that shows promise for nanoscale chemical characterization of biological–materials interactions. In an effort to apply this method to quantitatively probe mechanisms of microbiologically induced polyurethane degradation, we have investigated monolayer clusters of ∼200 nm thick Pseudomonas protegens Pf-5 bacteria (Pf) on a 300 nm thick polyether–polyurethane (PU) film. Here, the impact of the different biological and polymer mechanical properties on the thermomechanical AFM-IR detection mechanism was first assessed without the additional complication of polymer degradation. AFM-IR spectra of Pf and PU were compared with FTIR and showed good agreement. Local AFM-IR spectra of Pf on PU (Pf–PU) exhibited bands from both constituents, showing that AFM-IR is sensitive to chemical composition both at and below the surface. One distinct difference in local AFM-IR spectra on Pf–PU was an anomalous ∼4× increase in IR peak intensities for the probe in contact with Pf versus PU. This was attributed to differences in probe–sample interactions. In particular, significantly higher cantilever damping was observed for probe contact with PU, with a ∼10× smaller Q factor. AFM-IR chemical mapping at single wavelengths was also affected. We demonstrate ratioing of mapping data for chemical analysis as a simple method to cancel the extreme effects of the variable probe–sample interactions.